DETERMINAN KEBIJAKAN DIVIDEN DAN PENGARUHNYA TERHADAP STOCK PERFORMANCE (Studi Empiris pada Perusahaan yang terdaftar di Papan Utama tahun 2015-2017) - Margaretna, Margaretna (Jurnal KIAFE, 2020)
The purpose of this study is to examine and analyze the factors that influence dividend policy in companies. Variables used as determinants of dividend policy include financial performance, corporate debt policy and good corporate governance. In addition, this study also examines and analyzes the effect of a company's dividend policy on stock performance on the stock market as measured through stock returns and Sharpe indexes. In the study the object of observation was companies listed on the Main Board Index 2015-2017 of Indonesia Stock Exchange in 2016-2017.The research method used is multiple structural regression method, using the SmartPLS 3.0 technique. The purpose is due to several latent constructs in the research model and for the predictive effect on stock performance. The results showed that the independent variables of financial performance and good corporate governance had a positive and significant effect on dividend policy, corporate debt policy had a significant negative effect on dividend policy and the company's dividend policy had a significant positive effect on company stock performance.Daftar PustakaAbdillah, W. & Jogiyanto. 2014. Partial Least Square (PLS) Alternatid SEM dalam Penelitian Bisnis. Semarang: Penerbit Andi.Akerlof, G.A, 1970. The Market for “Lemons”: Quality Uncertainty and the Market Mechanism. The Quarterly Journal of Economics, Vol. 84, No. 3 pp 488-500 Alaghi, K. 2011. Financial Leverage and Systematic Risk. African Journal of Business Management, volume 5, issue 15, p. 6648 – 6650 Posted: 2011Arfan, M dan Maywindlan, T. 2013. Pengaruh Arus Kas Bebas, Collateralizable Assets, dan Kebijakan Utang Terhadap Kebijakan Dividen pada Perusahaan yang Terdaftar di Jakarta Islamic Index. Jauhar, A. 2014. Corporate Governance and Intellectual Capital on Firm Value of Banking Sector Companies Listed at Indonesia Stock Exchange in Period 2008-2012. Wacana Vol. 20 No. 1 (2017)Bhattacharya, S. 1979. Imperfect Information, Dividend Policy, and “The Bird inThe Hand” Fallacy. The Bell Journal of Economics. Vol. 10 No. 1 (Spring 1979): 259-270.Brigham, Eugene F., dan Joel F. Houston. 1998. Fundamental of FinancialManagement, Terjemahan Dodo Soeharto dan Herman Wibowo, Edisi VIII, Buku I, PT Golra Aksara Pratama, Penerbit Erlangga, Jakarta.Brigham, Eugene F. Joe F, Houston. 2001. Fundamental of Financial Management.Carlo, Michael Aldo. 2014. Pengaruh Return On Equity, Dividend Payout Ratio, Dan Price To Earnings Ratio Pada Return Saham. E-Jurnal Akuntansi, [S.L.], V. 7, N. 1, P. 150-164, Apr. 2014. ISSN 2302-8556.Dewi, R.P. et al. 2015. The Effects of Capital Structure and Good Corporate Governance on Dividend Policy and Firm Value. PROFIT: Jurnal Administrasi Bisnis Vol 9. No. 2 pp 51-59Dutta, A. et. al. 2012. Prediction of Stock Performance in the Indian Stock Market Using Logistic Regression. International Journal of Business and Administration. Vol 7 No. 1 pp. 105-136Easterbrook, F. 1984. Two agency-cost explanations of dividend. American Economic Review, 74, 650-659.Eisenhardt, K.M., 1989, Agency Theory: An Assessment and Review. The Academy of Management Review, Vol. 14 No.1 pp 57-74Fama, Eugene F. and French ,Kenneth R.. (1995). Size and Book-to-Market Factors in Earnings and Returns. The Journal of Finance.Vol. 50, No. 1 pp. 131-155Ghozali, I. 2017. Partial Least Squares Konsep, Teknik, dan Aplikasi Menggunakan Program SmarrPLS 3.0 Edisi 2, Semarang: Badan Penerbit Universitas Diponegoro.Gelb, David S. 1999. Corporate Signalling with Devidend, Stock Repurchase, and Accounting Disclosure: An Empirical Study. Journal of Accounting, Auditing and Finance, Hal. 99-120.Gordon, Myron and John Lintner. 1956. “Distribution of Income of Corporations Among Dividend, Retained Earning and Taxes”. The American Economic Review, May.Hair, J. F., Hult, G. T. M., Ringle, C. M., and Sarstedt, M. (2017). A Primer on Partial Least Squares Structural Equation Modeling (PLS-SEM), 2nd Ed., Sage: Thousand Oaks.Halviani, Made Dwi, danSisdiyani,EkaArdhani. 2014. Pengaruh Moderasi Good CorporateGovernance pada Return On Asset dan Dividend Payout Ratio. JurnalAkuntansi. Vol. 1 Th. 1 .pp. 1-5Harahap, Sofyan Syafri. (2011). Teori Akuntansi, Edisi revisi 2011. Raja Grafindo Persada: Jakarta.Herawati, V. (2008), “Peran Praktek Corporate Governance sebagai Moderating Variabel dari Pengaruh Earnings Management terhadap Nilai Perusahaan”, Simposium Nasional Akuntansi XI, IAI, Pontianak, Juli 23-24.Husnan, Suad. (2003). Dasar-Dasar Teori Portofolio dan Analisis Sekuritas.(Edisi 3). Yogyakarta : UPPN STIM YKPN.Indriantoro, N dan B. Supomo. 2009. Metodologi Penelitian Bisnis Untuk Akuntansi & Manajemen Edisi Pertama. Yogyakarta: BPFE.Jensen, M and W. Meckling. 1976. Theory of the firm: Managerial behavior, Agency cost, and Ownership structure. Journal of Finance Economic. Vol. 3, 305-360.Jensen, Solberg and Zorn. 1992. Simultaneous Determination of Insider Ownership, Debt and Dividend policies. Journal of Financial and Quantitative Analysis.Vol.27 No. 2.pp.247-263.Jogiyanto, 2014. Teori Portofolio dan Analisis Investasi (Edisi ke 10). Yogyakarta: BPFE.Kurniati, E. 2003. Analisis Pengaruh Dividend Payout Ratio, Current Ratio, Pertumbuhan Aset, dan Leverage terhadap Return Saham. Tesis Program Pascasarjana Universitas Diponegoro Semarang.Lakaba, A. dan Robiyanto. 2018. Evaluasi Kinerja Saham Bertanggungjawab Sosisal (Studi Pada Saham-saham yang Masuk Perhitungan Indeks SRI-Kehati). Jurnal Organisasi dan Manajemen Vol 14 No. 2, 95-107.Lindayani, NW. & Dewi, Sayu K.S. 2016. Dampak Struktur Modal Dan Inflasi Terhadap Profitabilitas Dan Return Saham Perusahaan Keuangan Sektor Perbankan. E-Jurnal Manajemen Vol 5 No. 8Li, Haidong and Zhang, H. 2017. The Correlation among Dividend Policy, Financial Performance and Stock Return Volatility. Journal of Dalian University of Technology (Social Sciences). Oktavina, M dan Majid, M.N. 2017. Analisis Kinerja Saham Individual pada Industri Farmasi di Bursa Efek Indonesia tahun 2016. Innovatio, Vol XVI no. 2.Muliawan, P.N, 2014. Faktor-Faktor yang Mempengaruhi Pengungkapan CSR pada Perusahaan yang Terdaftar pada Bursa Efek Indonesia Tahun 2012.Nuringsih, K., 2005. Analisis Pengaruh Kepemilikan Manajerial, Kebijakan Utang, ROA dan Ukuran Perusahaan Terhadap Kebijakan DividenL Studi 1995-1996. Jurnal Akuntansi dan Keuangan Indonesia Vol 2. Pp 103-123Rachmad, A.N. dan Muid, D. 2013. Pengaruh Struktur Kepemilikan, Leverage dan Return On Assets (ROA) Terhadap Kebijakan Dividen (Studi Empiris Pada Perusahaan Nonkeuangan Yang Terdaftar Di Bursa Efek Indonesia). Diponegoro Journal of Accounting. Vol 2. No. 3 pp. 1-11.Ringle, Christian M., Wende, Sven, & Becker, Jan-Michael. 2015. SmartPLS 3. Bönningstedt: SmartPLS. Retrieved from http://www.smartpls.comRobiyanto, R. 2017. Performance Evaluation and Risk Aversion Rate for Several Stock Indices in Indonesia Stock Exchange. Jurnal Manajemen dan Kewirausahaan. Vol 19 No. 1 hal 60-64.Robiyanto, R. & Hartanto, A.F. 2018. Contagion Effect dan Integrasi PasarModal di Kawasan Asia, Eropa dan Amerika. Jurnal Organisasi dan manajemen. Vol 14 No. 1, 1-10.Ross, Stephen A., Randolph W. Westerfield, Bradford D. Jordan. 2009. Pengantar Keuangan Perusahaan: Corporate Finance Fundamental. Edisi 8. Terjemahan oleh Ali Akbar Yulianto, dkk. 2008. Jakarta:Penerbit Salemba Empat.Rozeff, M. 1992 How Companies Set Their Dividend Payout Ratio. Di dalam Stern, J.M dan Chew, D.H. The Revolution in Corporate Finance. Blackwell Publishers. Oxford.Sari, D. 2004. Hubungan antara Konservatisme Akuntansi dengan Konflik Bondholders-Shareholders Seputar Kebijakan Dividen dan Peringkat Obligasi. Jurnal Akuntansi Indonesia Vol. 1 No. 2 pp. 63-88Sartono, Agus. 2001. Kepemilikan Orang dalam (Insider Ownership), Utang dan Kebijakan Dividen: Pengujian Empirik Teori Keagenan (Agency Theory), Jurnal Siasat Bisnis, Vol 2 No. 6.Yulianto, A et al. 2014. The Role of Corporate Governance, Dividend Policy and Capital Structure on Ownership Structure Toward the Firm Value. European Journal of Business and Management Vol. 6 No.8